2010
DOI: 10.1177/0093854810379969
|View full text |Cite
|
Sign up to set email alerts
|

First-Time and Recurrent Inmates’ Experiences of Imprisonment

Abstract: The authors surveyed 267 first-time (n = 102) and recurrent (n = 165) adult male inmates from two medium-security prisons in England. The findings revealed significant differences between the two groups of inmates: A relatively higher proportion of recurrent inmates were enrolled in drug treatment programs; a relatively higher proportion of first-time inmates had given up smoking and drinking, whereas more recurrent inmates had given up drugs; recurrent inmates thought about sex significantly more often, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 38 publications
1
33
1
1
Order By: Relevance
“…Alternatively, Patterson (2013) discovered that mortality risk increases with time served, and some study results have demonstrated a positive association between dosage and health-related outcomes such as feelings of hopelessness (Dhami, Ayton, & Loewenstein, 2007), psychiatric disorders (Baillargeon, Binswanger, Penn, Williams, & Murray, 2009), and body mass index (Houle, 2014). Finally, repeat bouts of incarceration may even be associated with improved health (Schnittker & John, 2007;Souza & Dhami, 2010).…”
mentioning
confidence: 99%
“…Alternatively, Patterson (2013) discovered that mortality risk increases with time served, and some study results have demonstrated a positive association between dosage and health-related outcomes such as feelings of hopelessness (Dhami, Ayton, & Loewenstein, 2007), psychiatric disorders (Baillargeon, Binswanger, Penn, Williams, & Murray, 2009), and body mass index (Houle, 2014). Finally, repeat bouts of incarceration may even be associated with improved health (Schnittker & John, 2007;Souza & Dhami, 2010).…”
mentioning
confidence: 99%
“…In documenting a personal journey, it can be argued that prisoners will find these handbooks more convincing and relevant through the empathy they convey. Whilst issues around literacy and language do need to be considered and alternative formats explored, we conclude by making a strong case for the prisoner handbook in its potential to aid adaptation to life in prison, which Souza and Dhami (2010) note, may contribute towards successful resettlement and have a positive impact not only on prisoners, but for all stakeholders in the criminal justice system.…”
Section: Discussionmentioning
confidence: 96%
“…There may also be implications for prison staff, to whom the task of correcting misinformation often falls. In addition, as noted by Souza and Dhami (2010), adaptation to life in prison can impact upon success post release. Therefore, given their potential to generate impact within and beyond prisons, it is clear that prisoner handbooks are deserving of academic scrutiny…”
mentioning
confidence: 99%
“…Jumlah ini melebihi kapasitas yang dialokasikan pemerintah; 27 dari 33 Kanwil di Indonesia menampung lebih banyak narapidana dari yang seharusnya (Sistem Database Pemasyarakatan; 23 Agustus 2017). Narapidana yang menjalani hukuman pertama kali memiliki perasaan takut dan kekhawatiran akan kekerasan dibandingkan dengan narapidana yang telah berulangkali masuk penjara (Souza & Dhami, 2010). Penelitian tentang dampak dari hukuman pidana yang lama (di atas enam tahun) oleh MacKenzie dan Goodstein (1985) menemukan bahwa narapidana yang dihukum pertama kali dan harus menjalankan hukuman di atas enam tahun mengalami tingkat kecemasan, depresi dan simtom psikosomatis yang lebih tinggi dibandingkan dengan narapidana yang menjalani hukuman di bawah enam tahun.…”
Section: Pendahuluan Latar Belakangunclassified